Ministerial Expert Committee Review of the WA Electoral system for the election of the Western Australian Legislative Council - Fullarton, Lex (Western Australian Government, 2021)
This submission is in response to a request by The Ministerial Expert Committee on Electoral Reform for submissions on the system used for the election of members to the Western Australian Legislative Council. It focuses on the Mining and Pastoral Electoral Region election results 2021 as that appears to be the primary influencing factor for the Attorney General and Minister for Electoral Affairs to commission the review.